The effect of mobile messaging on personality traits of housewives - Tayabeh mansourishad; ali delavar; afsane mozafari (مطالعات رسانه‌های نوین, 2019)
Nowadays, many housewives are using smart phones messging.The purpose of this paper  mobile messging effects on personality traits of housewives. Method:The study was all housewives in Tehran,that numer is 3039863 and volume of example according to Morgan table ,is 384 selected housewives which expleations how women were housewive  users  statistical society included all house wives in Tehran using multi-stage stratified sampling of 22 districts of Tehran . The technique to gather information of survey.Tofind the answer , The hypothesis proposed based Researcher-made qustionnair to  investigate  aspects  of behavior disordes  and  tool with 18 questions and scl90 scale.   The groups were compard based on independent t-test . the most important The effect of mobile messaging on personality traits of housewives. findings:In the end, there was significant relationship between two groups interm of physical complaints ,obsession,coercion, sentivity in interpersonal relationships , Axiety paranoid thouts , psychosis , aggression ,Depression(P<0/05) But there was not between two grous in term of phobia(p>0/05) . According to the results it is suggested the arrangement for managing this tool communication is previded among house wives users.Because according to thir positions in the management of formily in case of damage ,these people will affect the family.